PENGARUH KOMPETENSI DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PADA PT DOM PIZZA INDONESIA TANGERANG SELATAN - Nabila Hanif Khairunisa; Sutrisno (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of competence and work experience on employee performance at PT Dom Pizza Indonesia South Tangerang. This study uses quantitative methods with data collection techniques through distributing questionnaires. The population in this study was 73 employees. The sample used the entire population of 73 employees. The method used to analyze the validity test, reliability test, classical assumption test, simple and multiple linear regression, correlation coefficient test, determination and hypothesis testing with SPSS 26 software. The results showed that partially Competence has a significant effect on Employee Performance, it can be seen that the correlation value is 0.825, this value has a very strong relationship level. The coefficient of determination is 68.0% while the remaining 32.0% is influenced by other factors. The t test results obtained a tcount value of 12.280> t table 1.993 and a significant 0.000 <0.05. Work Experience has a significant effect on Employee Performance, it can be seen that the correlation value is 0.719, this value has a very strong relationship level. The coefficient of determination is 51.8% while the remaining 48.2% is influenced by other factors. The t test results obtained a tcount value of 8.729> t table 1.993 and a significant 0.000 <0.05. Simultaneously Competence and Work Experience have a positive and significant effect, this can be proven by the regression equation Y = 0.636X1 + 0.314X2, the correlation value of 0.848 means that the independent and dependent variables have a strong level of relationship, the coefficient of determination is 71.9% while the remaining 28.1% is influenced by other factors. Likewise, the results of the F test show Fhitung> Ftabel 89.342> 3.12 and a significant 0.000 <0.05 which means that competence and work experience have a significant effect on employee performance at PT Dom Pizza Indonesia South Tangerang.